EU Foreign Policy Towards Latin America - Dominguez, Roberto. author. aut Link
XI, 199 p. 1 illus.
Keywords: The second edition of EU Foreign Policy Toward Latin America systematically examines the main aspects of the EU-Latin America relationship. The chapters provide an in-depth analysis of the long-term trends in the EU's relationship with Latin America as a region, sub-regions, and individual countries. Students and practitioners interested in interregional studies, Latin America, and EU external relations will find this an invaluable resource to examine past interactions within the Euro-Latin American space. The book advances the concept of liberal partnerships, EU capacity building, and modular interregionalism, reflecting the convergence of strategic priorities, multiple narratives, and asymmetrical relations. Under one framework of analysis, the book explains why the EU and Latin America have developed a variety of institutional mechanisms of cooperation, ranging from bilateral association agreements to regional trade negotiations. Roberto Dominguez is Professor of International Relations at Suffolk University in Boston, Massachusetts, USA. He has been a Research Associate at the Center for European Studies at Harvard University and a Jean Monnet fellow at the European University Institute in Florence. His research interests are comparative regional governance and European Union-Latin American Relations.